Tantalum target material and preparation method and application thereof
By performing multi-step process processing on tantalum ingots, the grains are refined and the grain orientation ratio is increased, the problem of difficult control of the sputtering rate of tantalum targets is solved, and high-quality uniform deposition of tantalum films is achieved.
Patent Information
- Application Number
- CN202411600223.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The sputtering rate of existing tantalum targets is difficult to control during magnetron sputtering, resulting in poor uniformity of the tantalum film.
By performing multi-step processes such as annealing, cold forging, heat treatment, two-stage cross-rolling, static pressure treatment and recrystallization annealing on the tantalum ingots obtained from electron beam smelting, the grains are refined and the ratio of grain orientation is increased.
The grain distribution of tantalum targets is achieved more uniformly, finer grains, and higher grain orientation ratio, which reduces the sputtering rate and improves the uniformity of sputtering coating and film formation quality.
Smart Images

Figure BDA0005128087870000071
Abstract
Description
Technical Field
[0001] The invention belongs to the field of target material preparation, and in particular relates to a tantalum target material and a preparation method and application thereof. Background Art
[0002] In the chip manufacturing process, tantalum (Ta) film acts as a diffusion barrier for Cu interconnects, which can prevent copper atoms from diffusing into the Si matrix and causing a decrease in current density and component performance. Tantalum target material, as the raw material for sputtering Ta film, has gradually become one of the key raw materials in the semiconductor industry. Tantalum target material is formed into tantalum film by magnetron sputtering. Through physical vapor deposition technology (PVD), gaseous Ar ions are accelerated at high pressure to bombard the tantalum target material, so that the tantalum atoms or ion clusters on the tantalum target material are sputtered out and deposited on the silicon wafer in the form of a thin film. Tantalum is a body-centered cubic (BCC) metal and a high-layer dislocation metal. The internal structure, grain size and crystal orientation of the tantalum target material directly affect the quality of the film formed by magnetron sputtering. Generally, there are the following phenomena: (1) From the effect of grain orientation on sputtering rate (S), S{110}>S{100}>S{111}; (2) As the grain size increases, the film deposition rate tends to decrease; (3) Within the appropriate grain size range, the plasma impedance when the target is used is low, the film deposition rate is high and the film thickness uniformity is good. It can be seen that grain orientation and grain size are key factors affecting the target sputtering rate, film uniformity and overall quality. However, in the actual target preparation process, the control technology of grain, crystal orientation and sputtering rate is the key difficulty in the industry, resulting in very poor uniformity of the sputtered film. Summary of the invention
[0003] In view of the problem in the prior art that the sputtering rate of tantalum target is difficult to control, resulting in poor uniformity of tantalum film, the present invention will provide a tantalum target material and a preparation method and application thereof.
[0004] To achieve the above purpose, the following technical solutions are specifically included:
[0005] In one aspect, the present invention provides a method for preparing a tantalum target, comprising the following steps:
[0006] (1) annealing the tantalum ingot obtained by electron beam melting to obtain an annealed tantalum ingot;
[0007] (2) cold forging and heat treating the annealed tantalum ingot in sequence to obtain a forged tantalum ingot;
[0008] The cold forging comprises upsetting and drawing in sequence;
[0009] (3) The forged tantalum ingot is subjected to a first-stage cross rolling, a static pressure treatment, and a second-stage cross rolling in sequence to obtain a rolled tantalum ingot; in the static pressure treatment, the tantalum ingot after the first-stage cross rolling is deformed in the thickness direction; in the first-stage cross rolling, the rolling directions of two adjacent passes differ by 90°; in the second-stage cross rolling, the rolling direction of the first pass in the second-stage cross rolling differs by 45° to 135° from the rolling direction in the first stage, and the rolling directions of the two adjacent passes differ by 90°;
[0010] (4) Annealing the rolled tantalum ingot under vacuum conditions to obtain a tantalum target; the annealing treatment adopts a step-by-step heating method.
[0011] The tantalum ingots obtained by electron beam melting are annealed to remove stress in the tantalum ingots, reduce the risk of subsequent forging cracking, and provide a basis for subsequently reducing the grain size and increasing the proportion of {111} orientation.
[0012] The tantalum ingot is cold forged, which includes upsetting and drawing. This method can break the coarse columnar crystals in the cast state of the tantalum ingot and refine the grains. The orientation distribution in the grains is controlled by upsetting and drawing and the deformation rate. Heat treatment is performed after cold forging to control the orientation distribution and proportion of {111}, {110}, and {100}, so as to intervene and optimize the crystal orientation control in the subsequent rolling in advance.
[0013] Cross-rolling in different directions in two stages and static pressing during the two-stage cross-rolling can further refine the grains and significantly increase the proportion of the {111} orientation.
[0014] The rolled tantalum target blank is annealed in a step-by-step heating manner to achieve recrystallization, which can further increase the proportion of {111} orientation and refine the grains.
[0015] In the method of the present invention, the tantalum ingot is subjected to stress annealing, cold forging and heat treatment, two-stage rolling in different directions, intermediate static pressure treatment, and recrystallization annealing in sequence, and each step cooperates with each other, so that the grain distribution of the tantalum target material is more uniform, the grains are finer, and the proportion of the {111} grain orientation is higher; and by increasing the proportion of the {111} grain orientation, the sputtering rate is reduced to a certain extent, the sputtering stability can be increased, the uniformity of the sputtering coating is improved, and the purpose of improving the film quality is achieved.
[0016] Preferably, the purity of the tantalum ingot obtained by electron beam melting is ≥99.99wt%, more preferably 99.99wt%-999.995wt%.
[0017] Preferably, in step (1), the temperature of the annealing treatment is 1000-1400° C., and the time of the annealing treatment is 1-3 hours.
[0018] The tantalum ingot obtained by electron beam melting is annealed to remove stress in the tantalum ingot and reduce the risk of subsequent forging cracking. At the above-mentioned annealing temperature and time, the effect of removing stress is better.
[0019] Preferably, in step (2), the cold forging and heat treatment are performed sequentially 1 to 4 times.
[0020] The number of combined cold forging and heat treatment can further refine the grains, so that the cold forging and heat treatment cooperate with each other to improve the grains and their orientation as a whole.
[0021] Preferably, in step (2), in the cold forging, the number of upsetting and drawing is 1-4 times in sequence, the deformation rate of each upsetting is 20%-50%, and the deformation rate of each drawing is 30%-70%; the temperature of the heat treatment is 1000-1300°C, and the time of the heat treatment is 1-4h.
[0022] Cold forging includes 1-4 times of upsetting and drawing, while controlling the deformation rate, which can further break up the coarse grains in all directions and achieve the purpose of grain refinement.
[0023] Preferably, in step (2), the cold forging also includes rounding, and rounding during the cold forging process can increase the utilization rate of the subsequent target material.
[0024] Preferably, in step (3), in the first-stage cross-rolling and the second-stage cross-rolling, the total deformation rate is 65%-90%, and the total number of passes is 15-40.
[0025] Further preferably, in the first stage of cross-rolling, the total deformation rate is 40%-60%, and the total number of passes is 10-25.
[0026] Further preferably, in the second stage cross-rolling, the total deformation rate is 10%-40%, and the total number of passes is 10-20.
[0027] In each stage, increasing the number of rolling passes can further refine the grains to a certain extent, but the process cycle is increased.
[0028] Preferably, in step (3), in the first-stage cross-rolling and the second-stage cross-rolling, the rolling rates are each selected from 10-50 m / min, and the rolling mill diameters are each selected from above 500 mm.
[0029] Preferably, in step (3), during the static pressure treatment, the total deformation rate of the target material in the thickness direction is 10%-30%.
[0030] Preferably, in step (3), during the static pressure treatment, the pressure in the thickness direction is 1000-3000 tons.
[0031] The static pressure treatment of the present invention applies pressure only in the thickness direction. The static pressure treatment enables the tantalum ingot after the first stage cross rolling to be deformed in the thickness direction. Under the condition of controlling the above deformation rate, the proportion of {111} grain orientation can be significantly increased on the basis of obtaining lower grains.
[0032] Preferably, in step (4), the annealing temperature is 900-1200°C, the annealing time is 2-4h, and the step-wise heating method specifically includes the following steps: heating from room temperature to 300-500°C within 1-3h, and keeping warm for 1-2h; then continuing to heat to 1000-1200°C within 2-4h, and keeping warm for 2-4h
[0033] The step-by-step heating method under the above conditions is better in terms of grain refinement.
[0034] Preferably, in step (4), the vacuum degree of the vacuum condition is less than or equal to 5×e -3 Pa.
[0035] On the other hand, the present invention provides a tantalum target material obtained by the preparation method of the tantalum target material.
[0036] Preferably, the average grain size of the tantalum target grains is 60-80 μm, and the structure of the tantalum target on a cross section perpendicular to the sputtering surface is observed using electron backscatter diffraction, and the average area of grains oriented along the normal direction of the {111} plane is 25%-40%.
[0037] The inventors of the present invention have found that when the average particle size of the tantalum target grains is 60-80μm and the average area of the grains oriented along the normal direction of the {111} plane is 25%-40%, the sputtering rate can be reduced to a certain extent, the sputtering stability can be improved, and the uniformity and quality of the sputtering film can be improved.
[0038] In addition, the present invention also provides an application of the tantalum target material in the preparation of integrated circuits.
[0039] The tantalum target material of the present invention has uniformly distributed grains, a suitable average grain size, and a suitable ratio of {111} grain orientation. Under high-power sputtering conditions, the deposition rate of the sputtering coating is suitable, the film formation stability is high, and the uniformity of the sputtering coating is high, thereby meeting the requirements of high-quality semiconductor sputtering coating.
[0040] Compared with the prior art, the present invention has the following beneficial effects: in the method of the present invention, the tantalum ingot is subjected to stress annealing, cold forging and heat treatment, two-stage rolling in different directions, intermediate static pressure treatment, and recrystallization annealing in sequence, and each step cooperates with each other, so that the grain distribution of the tantalum target material is more uniform, the grains are finer, and the proportion of {111} grain orientation is higher, thereby controlling the sputtering rate and sputtering stability, improving the uniformity of the sputtering coating, and achieving the purpose of improving the film quality. DETAILED DESCRIPTION
[0041] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified.
[0042] The tantalum ingot obtained by electron beam melting used below has a purity of 99.995wt%, and the contents of W, Mo, and Nb are less than 10ppm. In the electron beam melting preparation process, the electron beam melting main high voltage is 35-50KV, the secondary high voltage is 1-3KV, the emission current is 2-5A, the temperature is 2800-3200℃, and the time is 3-6h. The same tantalum ingot is used in each embodiment and comparative example.
[0043] Example 1
[0044] A method for preparing a tantalum target comprises the following steps:
[0045] (1) annealing the tantalum ingot obtained by electron beam melting at 1300° C. and keeping the temperature for 2 hours to obtain an annealed tantalum ingot;
[0046] (2) subjecting the annealed tantalum ingot to two cold forging and heat treatment treatments in sequence to obtain a forged tantalum ingot; comprising the following specific steps:
[0047] (2-1) The annealed tantalum ingot is subjected to the first upsetting, and the upsetting deformation rate is 50%; the first drawing, and the drawing deformation rate is 70%; the second upsetting, and the upsetting deformation rate is 50%; the second drawing, and the drawing deformation rate is 70%; the third upsetting, and the upsetting deformation rate is 50%; the third drawing, and the drawing deformation rate is 70%;
[0048] (2-2) heat treatment at 1150°C for 2h;
[0049] (2-3) The annealed tantalum ingot is subjected to the first upsetting, with an upsetting deformation rate of 50%; the first drawing, with a drawing deformation rate of 70%; the second upsetting, with an upsetting deformation rate of 50%; the second drawing, with a drawing deformation rate of 70%; the third upsetting, with an upsetting deformation rate of 50%; the third drawing, with a drawing deformation rate of 70%;
[0050] (2-4) heat treatment at 1150°C for 2 h;
[0051] (3) subjecting the forged tantalum ingot to first-stage cross rolling, static pressing treatment, and second-stage cross rolling in sequence to obtain a rolled tantalum ingot;
[0052] Among them, the rolling mill selects a roller with a diameter of more than 500mm, the rolling speed is 25m / min, and the rolling is carried out at a temperature of 0-30℃ without heating, so it belongs to cold rolling; the specific process is as follows:
[0053] (3-1) In the first stage of cross rolling, the first pass is rolled in the 0° direction (the pressing amount each time is 1-10 mm, the same below), the second pass is rolled in the 90° direction, the third pass is rolled in the 0° direction, the fourth pass is rolled in the 90° direction, and so on. The rolling directions of the two adjacent passes differ by 90°, and a total of 20 passes are rolled. The total deformation rate in this stage is 50%;
[0054] (3-2) applying a static pressure of 1500 tons only in the thickness direction to the tantalum ingot after the first stage of cross rolling, so that the tantalum ingot achieves a deformation rate of 15% in the thickness direction;
[0055] (3-3) In the second stage of cross rolling, the first pass is rolled in the direction of 135° (or in the direction forming an angle of 135° with the direction of 90°), the second pass is rolled in the direction of 225° (forming an angle of 90° with the previous pass), the third pass is rolled in the direction of 135°, the fourth pass is rolled in the direction of 225°, and so on. The rolling directions of the two adjacent passes differ by 90°, and a total of 12 passes are rolled. The total deformation rate in this stage is 25%;
[0056] (4) The rolled tantalum ingot is placed under vacuum conditions (vacuum degree ≤ 5*E -3 Pa), annealing at 1050° C. to obtain a tantalum target;
[0057] The annealing treatment adopts a step-by-step heating method, which specifically includes the following steps:
[0058] The temperature was raised from room temperature (20°C) to 350°C within 2 hours and kept at this temperature for 1 hour; the temperature was further raised to 1050°C within 3 hours and kept at this temperature for 3 hours.
[0059] Example 2
[0060] The difference between this embodiment and embodiment 1 is that the annealing temperature in step (1) of this embodiment is 1000° C., and the rest of the process is the same.
[0061] Example 3
[0062] The difference between this embodiment and embodiment 1 is that the annealing temperature in step (1) of this embodiment is 1400° C., and the rest of the process is the same.
[0063] Example 4
[0064] The difference between this embodiment and embodiment 1 is that in step (3-2) of this embodiment, the tantalum ingot is deformed at a rate of 10% in the thickness direction, and the rest of the process is the same.
[0065] Example 5
[0066] The difference between this embodiment and embodiment 1 is that in step (3-2) of this embodiment, the tantalum ingot is deformed at a rate of 30% in the thickness direction, and the rest of the process is the same.
[0067] Comparative Example 1
[0068] The difference between this comparative example and Example 1 is that this comparative example lacks step (1) annealing treatment, and the rest of the processes are the same.
[0069] Comparative Example 2
[0070] The difference between this comparative example and Example 1 is that in step (2) of this comparative example, the static pressure treatment process of step (3-2) is not carried out, and the rest of the process is the same.
[0071] Comparative Example 3
[0072] The difference between this comparative example and Example 1 is that in step (3-3) of this comparative example, the direction of the cross-rolling in the second stage is the same as that in the first stage, which are combinations of 0° and 90° directions respectively, and the rest of the process is the same.
[0073] Tantalum target testing:
[0074] (1) Grain size: Use a metallographic microscope and analysis software to measure the average grain size;
[0075] (2) {111} orientation ratio: The test was performed using SEM and EBSD (electron backscatter diffraction) devices to obtain the organizational data diagram of the rolling surface normal (ND) direction of the cross section perpendicular to the target sputtering surface, and the {100} orientation analysis and report were performed using analysis software; among them, the grains with {111} plane oriented along ND include grains with an orientation deviation of {111} plane within 15° relative to the rolling surface normal (ND) direction.
[0076] Table 1
[0077]
[0078] It can be seen from the above embodiments that the average grain size of the tantalum target material prepared by the present invention is 60-80μm, and the average area of the grains oriented along the normal direction of the {111} plane is greater than 25% (25%-40%). The present invention reduces the sputtering rate and increases the sputtering stability to a certain extent by increasing the proportion of the {111} grain orientation, thereby improving the uniformity of the sputtering coating.
[0079] It can be seen from Example 1 and Comparative Examples 1-3 that the tantalum ingot obtained by electron beam melting is annealed to remove stress in the tantalum ingot, reduce the risk of subsequent forging cracking, and provide a basis for subsequently reducing the grain size and increasing the {111} orientation ratio; cross-rolling in different directions in two stages and static pressing treatment in the two-stage cross-rolling can further refine the grains and improve the {111} orientation distribution.
[0080] It can be seen from Examples 1-3 that the annealing temperature will also have a certain influence on the grain size and the {111} orientation ratio. The present invention can select 1000-1400°C for annealing. Within this range, the grain size is relatively small and the {111} orientation ratio is relatively high.
[0081] It can be seen from Examples 1-3 that the deformation rate during the static pressure treatment process will have a certain influence on the size of the grains and the proportion of the {111} orientation. The present invention can choose to use static pressure treatment to make the deformation rate of the tantalum ingot in the thickness direction reach 15%-30%. Within this range, the grain size is relatively small and the proportion of the {111} orientation is relatively high; if the deformation rate of the tantalum ingot in the thickness direction is too small through static pressure treatment, the degree of improvement of the {111} orientation proportion is not large; if the deformation rate is too large, the degree of improvement of the {111} orientation proportion is not large, and the required pressure is greater or the time is too long, resulting in low efficiency.
[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a tantalum target, characterized in that: The steps include: (1) annealing the tantalum ingot obtained by electron beam melting to obtain an annealed tantalum ingot; (2) cold forging and heat treating the annealed tantalum ingot in sequence to obtain a forged tantalum ingot; The cold forging comprises upsetting and drawing in sequence; (3) The forged tantalum ingot is subjected to a first-stage cross rolling, a static pressure treatment, and a second-stage cross rolling in sequence to obtain a rolled tantalum ingot; in the static pressure treatment, the tantalum ingot after the first-stage cross rolling is deformed in the thickness direction; in the first-stage cross rolling, the rolling directions of two adjacent passes differ by 90°; in the second-stage cross rolling, the rolling direction of the first pass in the second-stage cross rolling differs by 45° to 135° from the rolling direction in the first stage, and the rolling directions of the two adjacent passes differ by 90°; (4) Annealing the rolled tantalum ingot under vacuum conditions to obtain a tantalum target; the annealing treatment adopts a step-by-step heating method.
2. The method for preparing a tantalum target according to claim 1, characterized in that: In step (3), during the static pressure treatment, the total deformation rate of the target material in the thickness direction is 10%-30%.
3. The method for preparing a tantalum target material according to claim 1, characterized in that: In step (3), in the first-stage cross-rolling and the second-stage cross-rolling, the total deformation rate is 65%-90%, and the total number of passes is 15-40.
4. The method for preparing a tantalum target material according to claim 1, wherein: In step (1), the temperature of the annealing treatment is 1000-1400° C., and the time of the annealing treatment is 1-3 hours.
5. The method for preparing a tantalum target according to claim 1, wherein: In step (2), the cold forging and heat treatment are performed sequentially 1 to 4 times.
6. The method for preparing a tantalum target material according to claim 1, characterized in that: In step (2), during the cold forging, upsetting and drawing are performed 1-4 times in sequence, the deformation rate of each upsetting is 20%-50%, and the deformation rate of each drawing is 30%-70%; the temperature of the heat treatment is 1000-1300°C, and the time of the heat treatment is 1-4h.
7. The method for preparing a tantalum target according to claim 1, characterized in that: In step (4), the annealing temperature is 900-1200°C, the annealing time is 2-4h, and the step heating method specifically includes the following steps: heating from room temperature to 300-500°C within 1-3h, and keeping warm for 1-2h; then continuing to heat to 1000-1200°C within 2-4h, and keeping warm for 2-4h.
8. A tantalum target material obtained by the method for preparing a tantalum target material according to any one of claims 1 to 7.
9. The tantalum target material according to claim 8, characterized in that The average grain size of the tantalum target grains is 60-80 μm. The structure of the tantalum target on a cross section perpendicular to the sputtering surface is observed using electron backscatter diffraction. The average area of grains oriented along the normal direction of the {111} plane is 25%-40%.
10. Use of the tantalum target material according to claim 8 or 9 in the preparation of integrated circuit boards.
Citation Information
Patent Citations
Preparation method for high-performance tantalum sputtering target
CN105525263A
Ultra-pure tantalum with controllable tissues and textures and preparation method and application thereof
CN109338316A
Preparing method and application of cobalt tantalum zirconium alloy target material
CN110735068A
Ultrahigh-purity copper target material and grain orientation control method thereof
CN112921287A
Molybdenum sputtering targets
US20060042728A1